Surveying the biodiversity of the Cryptomycota using a targeted PCR approach. (April 2015) - Lazarus, Katherine L.; James, Timothy Y.
Abstract: Cryptomycota is a newly discovered phylum of early-diverging fungi that is estimated to comprise a massive amount of unstudied biodiversity. Known primarily from environmental DNA sequences, the group contains few formally described and successfully cultured genera, all known as obligate endoparasites. Numerous studies have detected Cryptomycota as DNA sequences in aquatic, terrestrial, and animal associated habitats, though no study to date has specifically targeted the group by PCR. In this study, we developed Cryptomycota-specific and preferential primers for the 18S rRNA gene in order to facilitate studies on the biodiversity and ecology of the group. The diversity of sequences and habitat association of Cryptomycota was surveyed across three environments: freshwater sediment, marine sediment, and soil. The new primers were able to recover a large proportion of Cryptomycota sequences: of 56 sequences cloned or directly sequenced, 44 were unique OTUs and (39/44) 88.6 % were phylogenetically affiliated with Cryptomycota. This study expands the boundary of current Cryptomycota sequence diversity; unique Cryptomycota OTUs were spread across six of 12 supported Cryptomycota sub clades. Freshwater sediments and soil were consistently amplified with the Cryptomycota-preferential primers. Our results suggest that Cryptomycota are ubiquitous and phylogenetically diverse components of essentially all terrestrial and aquatic ecosystems, whose ecological functions should be better explored.